THE LEVEL OF DENTAL AND ORAL HEALTH KNOWLEDGE ON TEACHERS AND STUDENTS AT SDN 16 (UKGS) AND SDN 46 (NON-UKGS) IN BANDA ACEH - Novita, Cut Fera; wanda, Her; ajir, Muh (FKG Universitas Syiah Kuala, 2018)
Knowledge on the dental and oral health provides comprehension how to perform maintenance and efforts to prevent dental and oral diseases. Teachers can take on the role as a source of information for students that are expected to have enough knowledge about dental and oral health which is applied in the UKGS program. The aim of this study was to know how the level of knowledge of dental and oral health on teachers and students in primary schools with and without UKGS. The study was descriptive. Subject retrieval technique used total sampling with the total study subjects who met the inclusion criteria by 69 people from 39 teachers and 80 students, consists of 24 teachers and 64 students from SDN 16 (UKGS) then 15 teachers and 16 students from SDN 46 (non-UKGS). Measuring the level of dental and oral health knowledge conducted using questionnaires. The results of study showed that the level of dental and oral health knowledge on teachers and students in SDN 16 (UKGS) and SDN 46 (non-UKGS) had a good category with percentage of 87.5% for teachers and 82,8% for students in SDN 16 (UKGS) and 80% for teachers and 68,8% for students in SDN 46 (nonUKGS). Keywords: UKGS, knowledge, teachers, students